Social fluency for autism: a caretaker's handbook - Hassan, Muhamad Hafiz (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Navigating social situations can be incredibly challenging for children with autism spectrum disorder (ASD). Mastering skills like reading body language, taking turns in conversation, making friends, and dealing with discomfort are mysteriously complex for those with ASD. This confusion surrounding social interaction can lead to isolation, anxiety, and distress. In indispensable guide "Navigating Social Situations," Muhamad Ha draws upon his extensive experience as an ASD specialist to chart a course to social confidence. With care and compassion, he addresses the unique needs of children on the spectrum. He provides concrete training techniques, visual aids, and step-by-step instructions specifically tailored for autistic learning strengths. This holistic toolkit prepares both children and caretakers for incremental success in real world social scenarios. Muhamad Ha explores potential sensory issues and meltdown triggers, advising thoughtful management strategies. He offers wisdom surrounding healthy identity development and self-advocacy - empowering neurodiverse children to communicate their needs. With the lessons in this essential handbook, children with ASD can progress from social confusion to communication clarity. Witness firsthand how methodical support, encouragement, and understanding can unlock any child's fullest potential. Let this book chart the path forward to social fluency. He tried to highlight the key goals and themes of the book while speaking to both a parent and professional audience who would be interested in purchasing the book. Please let me know if you would like him to modify or expand the editor's note further.